Information Overload In The Workplace: Perspective Of Multinational Corporation Knowledge Workers In Malaysia - Ling, Ooi Chen (2011)
With the current acceleration of information technology and communication, knowledge workers have to deal with more information while expecting to do more with less time. In Multinational Corporations (MNC) especially, where the workplace is highly dependent on information technology and organization structure is more complex, spanning across multiple countries - more and more MNCs see Information Overload in the workplace as a serious issue and are investing on countermeasures to manage its cumulative effect and to prevent damage to organizational efficiency.